Genotyping and diversity analysis of local avocado landraces in La Palma, Canary Islands - Pérez, Verónica; Larranaga, Nerea; Alcaraz, M. Librada; Hormaza, J. Ignacio (Frontiers in Plant Science, 2025)
Although both informal and formal avocado breeding has been carried out for over a century, current commercial avocado production worldwide is concentrated on only a few cultivars, with ‘Hass’ dominating the global avocado market. This narrow genetic base hinders the long-term sustainability of the crop amid the challenges derived from climate change. For this reason, studying the existing avocado diversity is essential and, in this work, we address this issue by analyzing the genetic diversity of 177 avocado trees from La Palma, Canary Islands, and comparing it with 89 avocado accessions maintained at a worldwide avocado germplasm bank in Málaga, Spain. In the Canary Islands, particularly on the island of La Palma, local avocado germplasm can be found due to the historic commercial and cultural ties with America that have lasted for over 500 years. Currently, isolated avocado trees that originated from or descended from these transoceanic movements still persist. Using nine SRR molecular loci, we characterized these isolated trees that have adapted to insular conditions and often predate commercial varieties. The analyses grouped the samples by racial origin and revealed a high percentage of interracial hybrids, likely resulting from seeds exchange between farmers and free pollination.